2002
DOI: 10.1097/00008571-200208000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter gene and response to methylphenidate in attention-deficit/hyperactivity disorder

Abstract: This study aims to evaluate whether a previously reported association between homozygosity for the 10-repeat allele of the dopamine transporter gene (10/10) and poor response to methylphenidate (MPH) would be replicated in a sample of Brazilian attention deficit/hyperactivity disorder (ADHD) boys. In a blind naturalistic study, 50 male ADHD youths were treated with MPH. Efficacy of the medication was measured by means of the 10-item Conners Abbreviated Rating Scale (ABRS), and the Children's Global Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
115
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 12 publications
11
115
1
3
Order By: Relevance
“…The earliest studies reported an association between homozygosity of the 10-repeat allele and poor response to MPH. In addition to being naturalistic, these studies were based on small numbers of patients and grouped patients with 9/9 and 9/10 genotypes (Winsberg and Comings, 1999;Roman et al, 2002). A subsequent retrospective naturalistic study conducted on a sample of 119 patients reported an overtransmission of the 10-repeat allele from parents to children with good response to MPH (Kirley et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The earliest studies reported an association between homozygosity of the 10-repeat allele and poor response to MPH. In addition to being naturalistic, these studies were based on small numbers of patients and grouped patients with 9/9 and 9/10 genotypes (Winsberg and Comings, 1999;Roman et al, 2002). A subsequent retrospective naturalistic study conducted on a sample of 119 patients reported an overtransmission of the 10-repeat allele from parents to children with good response to MPH (Kirley et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The pooled odds ratio derived from family-based association studies was reported to be 1:13 with 95% confidence interval ¼ [1.03-1.24] . Four published studies have investigated the relation between the 3 0 -UTR VNTR alleles/genotypes and therapeutic response to MPH (Winsberg and Comings, 1999;Roman et al, 2002;Kirley et al, 2003;Stein et al, 2005). Although each of these studies reported positive findings, there was no consistency with regard to the effect of each allele/genotype on therapeutic response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have examined the role of naturally occurring DAT variants in the clinical response to methylphenidate, but results from these studies are not entirely consistent. While some studies show no difference in response to methylphenidate among groups of individuals with different DAT polymorphisms (Mick et al, 2006;van der Meulen et al, 2005;Zeni et al, 2007), other studies have shown an association between DAT polymorphism and the response to methylphenidate, but not always in the same direction (Cheon et al, 2005;Kirley et al, 2003;Roman et al, 2002;Winsberg and Comings, 1999). The DAT KO mouse has been examined for a number of behaviors.…”
Section: Cell Support and Signaling Proteins: Amphetamine And Methamphementioning
confidence: 99%
“…The 10-repeat allele of a variable number of tandem repeats (VNTR) situated in the 3 0 untranslated region of the DAT1 gene (mapping to 5p15.3) has been associated with the clinical ADHD phenotype in a number of studies (Cook et al, 1995;Gill et al, 1997;Daly et al, 1999). This variant may confer an enhanced therapeutic response to methylphenidate (MPH) (Kirley et al, 2003; but see Winsberg and Comings, 1999;Roman et al, 2002). Here, we ask whether an attentional phenotype is related to (a) genetic variation in the DAT1 VNTR and (b) the therapeutic efficacy of MPH in ADHD.…”
Section: Introductionmentioning
confidence: 99%